POJOK BACA SEBAGAI SARANA LITERASI SISWA SEKOLAH DASAR - Marselina Jupon, Rara; Septia Negara, Erliza (YHMM PUBLISHING, 2024)
The Reading Corner as a literacy tool for elementary school students aims to increase reading interest and literacy skills from an early age. This research was conducted as an effort to foster a reading culture in the school environment and form a generation that has good literacy skills. The Reading Corner provides a variety of interesting and age-appropriate books for children, including story books, encyclopedias and general knowledge books. In this outreach, teachers, students and parents are actively involved to support the creation of reading habits at home and at school. Through this reading corner, it is hoped that a young generation who is intelligent, critical and has a high curiosity can be formed. This Reading Corner is part of the national literacy program which supports better educational attainment, especially in terms of reading and writing skills.